Vagal nerve signals are modulated by spontaneous seizures in Genetic Absence Epilepsy Rats from Strasbourg - Elise Collard; Enrique Germany Morrison; Enrique Germany Morrison; Elena Acedo Reina; Ayse S. Dereli; Auriane Apaire; Auriane Apaire; Antoine Nonclercq; Riem El Tahry; Riem El Tahry; Riem El Tahry (Frontiers in Neuroscience, 2025)
IntroductionOne-third of epileptic patients are resistant to conventional treatments. Vagus nerve stimulation is a promising therapy, especially when applied early during seizure onset. This study explores vagus nerve activity (VNA) during seizures in Genetic Absence Epilepsy Rat from Strasbourg (GAERS) model and explores how VNA changes with epilepsy duration.MethodsEleven rats (4, 6, and 10 months old, n = 4, 4, 3, respectively) were continuously recorded with electroencephalography, VNA recordings, and video for 24 h. Ictal VNA root mean square (RMS) values preceded by NREM sleep extracted from 11 rats were studied in a total of 620 seizures.ResultsOverall, VNA RMS increased during seizures, with a median rise of 60%. However, this modulation decreased with age, despite stable seizure severity. Significant differences in VNA activity and inter-quartile range were observed between age groups.DiscussionThese results support seizure severity-dependent changes in ictal VNA modulation and point toward the potential of VNA as a biomarker for seizure detection and autonomic dysfunction.